2021
DOI: 10.1136/openhrt-2021-001687
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interventions to increase physical activity for people with heart failure: a meta-analysis

Abstract: ObjectivesThis meta-analysis aims to (1) evaluate the efficacy of physical activity interventions in heart failure and (2) to identify intervention characteristics significantly associated with the interventions’ efficacy.MethodsRandomised controlled trials reporting intervention effects on physical activity in heart failure were combined in a meta-analysis using a random-effect model. Exploratory meta-analysis was performed by specifying the general approach (eg, cardiac rehabilitation), strategies used (eg, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…Older age is a barrier to physical activity in HF, as suggested by both qualitative and quantitative evidence. This result further reiterated the finding of a meta-analysis (Amirova et al, 2021) that older adults living with HF need more support to attain higher physical activity levels.…”
Section: Contextual Barriers and Enablerssupporting
confidence: 65%
See 3 more Smart Citations
“…Older age is a barrier to physical activity in HF, as suggested by both qualitative and quantitative evidence. This result further reiterated the finding of a meta-analysis (Amirova et al, 2021) that older adults living with HF need more support to attain higher physical activity levels.…”
Section: Contextual Barriers and Enablerssupporting
confidence: 65%
“…Finally, tentative suggestions are made for what a future physical activity intervention needs to include Overall, the review findings indicate that to reduce the barriers and enhance the enablers, a behaviour change intervention containing the following BCTs are needed: identity associated with target behaviour, prompt/cues and adding objects to the environment, behavioural practice/rehearsal, and graded tasks. A previous meta-analysis of randomised controlled trials also suggested that these strategies are associated with the efficacy of interventions (Amirova et al, 2021). In addition, the qualitative evidence included in this review suggests that addressing the change in the social identity as a result of acquired HF diagnosis and the perceived appropriateness of physical activity in this context need to be addressed.…”
Section: Recommendations For Future Research and Clinical Practicementioning
confidence: 90%
See 2 more Smart Citations
“…Planning is especially important among clinical population groups because identified reasons for dropouts include irregularity (lack of consistency), low automaticity, and self-regulation (planning) [53], which reflect the importance and the presence of these variables in this study. While investigations are limited among individuals with acute coronary syndrome, planning has been found to be an effective behavior change technique for people with heart failure [54].…”
Section: Behavioral Maintenance Constructsmentioning
confidence: 99%